Evaluating the reality of total quality management in the Hajj and Umrah - Rawas, Hasan Siraj (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the reality of total quality management in catering and subsistence establishments in Makkah from the point of view of administrators and workers. The researcher used the descriptive analytical approach, and the study population was represented by the 115 kitchens in Makkah Al-Mukarramah, and the study sample was chosen from workers and administrators in those kitchens. The researcher has come to many findings, the most important are: The catering and catering establishments in Makkah implement Total Quality Management.The senior management of catering establishments is committed to the success of total quality management. In the light of these results, the researcher recommended: The need for the higher management of the catering institutions in Makkah to provide all the necessary resources for the appropriate development and continuous improvement of their systems. The necessity of involving workers in the strategic planning process.